The RISK MANAGEMENT MATURITY, ITS DETERMINANTS AND IMPACT ON FIRM VALUE: EMPIRICAL EVIDENCE FROM JOINT-STOCK COMPANIES IN BOSNIA AND HERZEGOVINA (The South East European Journal of Economics and Business, 2021)
The current extremely volatile business environment requires companies to manage a wide range of risks. Poor management of the company’s main risks can lead to significant value losses for key stakeholders. Companies strive to preserve and protect their value by developing risk management models based on organisational culture, processes and structure. The main objective of this paper is to assess the maturity of risk management, explore its determinants and examine its impact on firm value. In order to quantify the maturity of the risk management model, we have created an index based on 31 reference components whose weighting values have been determined by a group of experts using the Delphi technique. In addition, this paper aims to identify the determinants of the risk management model maturity in companies in Bosnia and Herzegovina (B&H). Based on the estimated ordinary least squares (OLS) model, the results confirm that companies from the financial sector have more mature risk management models compared to the real sector. Moreover, the size of the firm and the type of auditor were identified as additional determinants of risk management maturity. The OLS model confirms the positive and statistically significant impact of risk management model maturity on Tobin’s Q value.